2016
DOI: 10.1534/g3.116.030338
|View full text |Cite
|
Sign up to set email alerts
|

A Genomic Analysis of Factors Driving lincRNA Diversification: Lessons from Plants

Abstract: Transcriptomic analyses from across eukaryotes indicate that most of the genome is transcribed at some point in the developmental trajectory of an organism. One class of these transcripts is termed long intergenic noncoding RNAs (lincRNAs). Recently, attention has focused on understanding the evolutionary dynamics of lincRNAs, particularly their conservation within genomes. Here, we take a comparative genomic and phylogenetic approach to uncover factors influencing lincRNA emergence and persistence in the plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 69 publications
6
38
0
1
Order By: Relevance
“…Although the functional characterization of lncRNAs is confined to a small number of cases, plant lncRNAs are being reported at a rapidly increasing pace (Nelson et al, 2016). As in the case of animals, it is important therefore find evidence for the functionality of individual transcripts.…”
Section: Introductionmentioning
confidence: 99%
“…Although the functional characterization of lncRNAs is confined to a small number of cases, plant lncRNAs are being reported at a rapidly increasing pace (Nelson et al, 2016). As in the case of animals, it is important therefore find evidence for the functionality of individual transcripts.…”
Section: Introductionmentioning
confidence: 99%
“…tauschii. In fact, both processed and unprocessed (those that no longer have a recognizable parental gene) pseudogenes, when transcribed, can be functional through the production of lncRNAs (Milligan and Lipovich 2014 (Nelson et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We suggest starting at an E-value cutoff of 1E-20 because we found that, across 10 Brassicaceae genomes, and independently between human, orangutan and mouse, this value was optimal for recovering reciprocal and syntenic sequence homologs (Nelson et al, 2016).…”
Section: Identifying Lincrna Conservation With Evolinc-iimentioning
confidence: 99%
“…Evolinc-II is an automated and improved version of a workflow we previously used to determine the depth to which Liu-lincRNAs (Liu et al, 2012) were conserved in other species of the Brassicaceae (Nelson et al, 2016). The Evolinc-II workflow is outlined in Figure 2A.…”
Section: Evolinc-ii Validationmentioning
confidence: 99%